THE ROLE OF EZIO’S STRUGGLE IN ITALIAN REVOLUTION ERA IN OLIVER BOWDEN’S ASSASSIN’S CREED RENAISSANCE - BUDIASTA, REDY LUHUR (Jurnal Ilmiah Mahasiswa FIB, 2013)
Keywords:  Assassin’s Creed Renaissance,  Assassin,  Templar, ItalianRenaissance, Manifestation of Struggle, Historical Approach  Renaissance is one of the most crucial moments in human civilization history. In this era, the art, science, and technology developed significantly, and people were gaining their freedom to stand between worldly and religion purpose. Assassin’s Creed Renaissance is a historical-fictional novel which elevated the Italian Renaissance theme and the author, Oliver Bowden, illustrates it by exposing the main character action, Ezio Auditore, in struggling for freedom and justice. The application of historical approach in this study is to dig out how important the role of Ezio and his allies to influence the revolution of Italy. Furthermore, it used to explore the conflict between Assassin and Templar, and find the comparison between the fictional evidence and the fact in historical record to clarify the analysis. The result of the study  discovers  that  Oliver Bowden’s  Assassin’s Creed Renaissance  elaborates  the effort of Ezio and his allies as a process to reach a revolution. Various conflicts between Assassin and Templar are clearly described in the novel. Likewise the combination of historical fact and fictional aspect is also successfully described. As the first novel of  Assassin’s Creed  franchise, the next researchers who are interested in revolution concept can do a research to another novel, or even the newest one, Assassin’s Creed Forsaken using the same perspective.